2020
DOI: 10.3389/fmicb.2020.00359
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Drug Tolerance of Mycobacterium abscessus “Persisters”

Abstract: Persistence of infection despite extensive chemotherapy with antibiotics displaying low MICs is a hallmark of lung disease caused by Mycobacterium abscessus (Mab). Thus, the classical MIC assay is a poor predictor of clinical outcome. Discovery of more efficacious antibiotics requires more predictive in vitro potency assays. As a mycobacterium, Mab is an obligate aerobe and a chemo-organo-heterotroph -it requires oxygen and organic carbon sources for growth. However, bacteria growing in patients can encounter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
72
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 41 publications
(51 reference statements)
9
72
0
1
Order By: Relevance
“…We used equimolar concentrations of clarithromycin and amikacin in our experiments and found that clarithromycin was more potent in reducing the bacterial burden of macrophages. This result is consistent with the lower minimum inhibitory concentration of clarithromycin in broth culture of M. abscessus Bamboo (200 μM vs. 2 μM) [ 31 ]. Furthermore, clarithromycin (in contrast to amikacin) is known to accumulate in macrophages [ 32 ], which likely also contributes to the observed differential potencies of the two drugs.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…We used equimolar concentrations of clarithromycin and amikacin in our experiments and found that clarithromycin was more potent in reducing the bacterial burden of macrophages. This result is consistent with the lower minimum inhibitory concentration of clarithromycin in broth culture of M. abscessus Bamboo (200 μM vs. 2 μM) [ 31 ]. Furthermore, clarithromycin (in contrast to amikacin) is known to accumulate in macrophages [ 32 ], which likely also contributes to the observed differential potencies of the two drugs.…”
Section: Resultssupporting
confidence: 86%
“…M. abscessus Bamboo strain is a smooth colony morphotype derived from a clinical isolate. We have chosen the Bamboo strain as its whole genome has been sequenced [ 30 ], it has been used as a screening strain for M. abscessus drug discovery [ 16 ], and the strain was characterized in a range of “persister assays” [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similar to our findings, they found that amikacin exhibited bactericidal activity in these conditions, while clarithromycin, imipenem, and linezolid had no bactericidal activity. Yam et al directly compared the 2-day MBC (>1 log 10 CFU/mL kill) of drugs against actively-growing M. abscessus strain Bamboo and against bacteria that had been nutrient-starved in PBS with tyloxapol for 6 days prior to drug exposure (10). Overall, we reported similar findings for clofazimine, imipenem, amikacin, clarithromycin, and linezolid.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to better understand how to maximize the use of currently available drugs for treatment of M. abscessus lung disease, we evaluated bactericidal activity against both actively multiplying and net non-replicating M. abscessus populations. Berube et al and Yam et al have also previously considered the importance of evaluating drug activity against non-replicating M. abscessus , and developed assays to generate populations of non-replicating M. abscessus via nutrient starvation in phosphate-buffered saline (PBS) for 4 or 6 days (9, 10). While induction of a non-replicating state by nutrient starvation cannot possibly represent all the different in vivo niches that might limit bacterial multiplication and induce a persister phenotype, it is one of several standard in vitro “persister” assays regularly used in TB drug development (6).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the chronic nature of M. abscessus infections, as well as prolonged sub-lethal concentrations of antimicrobials, drives induced (mutation based) antibiotic resistance, further limiting antibiotic choices and requiring multi-antimicrobial therapy. Even when the effective concentration of antimicrobials is well above the MIC, M. abscessus killing is limited due to antibiotic tolerance, especially related to biofilm formation [2,3], therefore adding difficulty in the successful treatment of these patients.…”
Section: Introductionmentioning
confidence: 99%